Analysis of the Childfree Phenomenon in South Korea Society Through Frankfurt School Perspective - Putra, Putu Oka Astama Adi; Simatupang, Zakharia Billy Aprilius; Matias, Raynold (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
Industrialization entered South Korea in 1973 and by 1986 the number of South Korean industrial workers had doubled compared to 1971. This was due to the labor market policies put in place by Park Chung Hee regime, which encouraged the mobilization of the younger generation to big cities. This policy then affects and changes the values of society and families in South Korea. South Korean society, which previously honored family values, has become individualistic for several reasons, such as their orientation towards work. These conditions then create several phenomena in South Korean urban society, such as the emergence of childfree families in South Korea. The purpose of our research is to understand how industrialization can affect family values in South Korea. The research method used is qualitative research with a case study approach, and uses the Frankfurt School perspective with data sources of articles, journals, and news. This study found that industrialization can affect family values because of the labor market and community mobilization that occurs in South Korea. In order to fulfill production activities, not only men but also women enter the labor market. In its development, this study found the change in society's behavior towards childbearing, due to the high cost of raising children, society's orientation towards work, and discrimination against women in the workplace. This condition according to Frankfurt School is then called as irrationality in society and creates childfree phenomena in families in South Korea.